PHYSICAL MODELLING OF TERRAIN DIRECTLY FROM SURFER GRID AND ARC/INFO ASCII DATA FORMATS - Modi, Y K; de Beer, D J; Agrawal, S (South African journal of industrial engineering, 2012)
Additive manufacturing technology is used to make physical models of terrain using GIS surface data. Attempts have been made to understand several other GIS file formats, such as the Surfer grid and the ARC/INFO ASCII grid. The surface of the terrain in these file formats has been converted into an STL file format that is suitable for additive manufacturing. The STL surface is converted into a 3D model by making the walls and the base. In this paper, the terrain modelling work has been extended to several other widely-used GIS file formats. Terrain models can be created in less time and at less cost, and intricate geometries of terrain can be created with ease and great accuracy. [PUBLICATION ABSTRACT]